Evaluation On Pathogenicity Of Entomopathogenic Fungi Metarhizium Anisopliae On The Rove Beetle, Paederus Fuscipes Curtis - Tan, Andy Fu Hao (2018)
Rove beetle, Paederusjuscipes Curtis is a natural predator of several crop pests in agricultural ecosystem, however their high intrusion into human settlements causes them to become a public health concern due to Paedarus dermatitis infection among human. This study was undertaken to investigate the effectiveness of Metarhizium anisopliae fungi as a biocontrol agent for P. fuscipes, The pathogenicity of entomopathogenic fungi, Metarhizium anisopliae against the beetle P. fuscipes were tested using three teclmiques; soil infection, bait infection, and horizontal transmission via endo-cannibalistic behaviour.